2020
DOI: 10.3390/v12111270
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Circular and Highly Asymmetrical Marseilleviridae Genomes

Abstract: Marseilleviridae members are large dsDNA viruses with icosahedral particles 250 nm in diameter infecting Acanthamoeba. Their 340 to 390 kb genomes encode 450 to 550 protein-coding genes. Since the discovery of marseillevirus (the prototype of the family) in 2009, several strains were isolated from various locations, among which 13 are now fully sequenced. This allows the organization of their genomes to be deciphered through comparative genomics. Here, we first experimentally demonstrate that the Marseilleviri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…The time-course transcriptome analysis of A. castellanii cells infected by Marseillevirus was performed using the RNA-seq data from ( Rodrigues et al., 2020 ). We first annotated the Marseillevirus genome (accession GU071086) as described ( Blanca et al., 2020 ), as well as the A. castellanii Neff host genome (assembly GCA_000193105.1) using the Funannotate pipeline (version 1.7; https://github.com/nextgenusfs/funannotate ). We then mapped the RNA-seq reads corresponding to 30 min pi (ERR3528397), 1 h pi (ERR3528398), 2 h pi (ERR3528399), 4 h pi (ERR3528400), 5 h pi (ERR3528401), 6 h pi (ERR3528402), 8 h pi (ERR3528403), 10 h pi (ERR3528404) and 12 h pi (ERR3528405) to the host and viral transcripts using Bowtie ( Langmead and Salzberg, 2012 ) (version 2.3.4.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time-course transcriptome analysis of A. castellanii cells infected by Marseillevirus was performed using the RNA-seq data from ( Rodrigues et al., 2020 ). We first annotated the Marseillevirus genome (accession GU071086) as described ( Blanca et al., 2020 ), as well as the A. castellanii Neff host genome (assembly GCA_000193105.1) using the Funannotate pipeline (version 1.7; https://github.com/nextgenusfs/funannotate ). We then mapped the RNA-seq reads corresponding to 30 min pi (ERR3528397), 1 h pi (ERR3528398), 2 h pi (ERR3528399), 4 h pi (ERR3528400), 5 h pi (ERR3528401), 6 h pi (ERR3528402), 8 h pi (ERR3528403), 10 h pi (ERR3528404) and 12 h pi (ERR3528405) to the host and viral transcripts using Bowtie ( Langmead and Salzberg, 2012 ) (version 2.3.4.1).…”
Section: Methodsmentioning
confidence: 99%
“…The time-course transcriptome analysis of A. castellanii cells infected by Marseillevirus was performed using the RNA-seq data from (Rodrigues et al, 2020). We first annotated the Marseillevirus genome (accession GU071086) as described (Blanca et al, 2020), as well as the A. castellanii Neff host genome (assembly GCA_000193105.1) using the Funannotate pipeline (version 1.7; https://github. com/nextgenusfs/funannotate).…”
Section: Marseillevirus-acanthamoeba Castellanii Transcriptomementioning
confidence: 99%
“…Such an unequal distribution of core genes is also observed among NCLDVs with a circular genome [88]. Among the members of Marseilleviridae , the core gene regions are concentrated in a region covering one-third of the genome, in which genome rearrangements are nearly absent and primary sequence slightly more conserved [88].…”
Section: Ncldv Comparative and Evolutionary Genomics – A View From Protein Familiesmentioning
confidence: 99%
“…The extremities of NCLDV genomes can also contain members of some conserved gene families, but their synteny and orientation are typically not conserved [87]. Such an unequal distribution of core genes is also observed among NCLDVs with a circular genome [88]. Among the members of Marseilleviridae , the core gene regions are concentrated in a region covering one-third of the genome, in which genome rearrangements are nearly absent and primary sequence slightly more conserved [88].…”
Section: Ncldv Comparative and Evolutionary Genomics – A View From Protein Familiesmentioning
confidence: 99%
“…A recent study conducted on the noumeavirus DNA confirmed by pulse-field gel electrophoresis and restriction digestion that its genome is circular ( Blanca et al, 2020 ). In addition, these authors conducted a comparative genomic study to analyze the organization of the marseillevirus genomes and reported an asymmetry in sequence conservation along these genomes.…”
Section: Genomic Study Of Marseillevirusesmentioning
confidence: 99%